Antioxidant Activity and Anti-inflammation Action of Orchid leaf ethanol Extracts - Yoon, Mi-yun; Moon, Ji-sun; You, Seon-hee (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: Orchid has excellent efficacy in the treatment of antioxidants and is widely used in folk remedies Therefore, we want to observe the possibility of implantation as an additive to cosmetics.Methods: Cell toxicity tests were performed to observe the safety of the orchid leaf ethanol extracts, and DPPH solution was used to observe the antioxidant power of the components themselves. The effect of fluorescence on the expression of DCF-DA was observed. The anti-inflammatory efficacy was observed by observing the potential as an inhibitor of NO produced by inflammatory reactions.Findings: Orchid leaf ethanol extracts was considered to be a safe substance because it did not show cytotoxicity, and DPPH was used to suppress oxidative stress inhibition in a concentration-dependent manner. Inhibition of ROS production in RAW 264.7 cells expressed in the fluorescent substance DCF-DA showed excellent antioxidant activity of the ethanol extract of orchid leaves. NO production was inhibited in LPS- induced RAW 264.7 cells but weakly at low concentrations. However, as the concentration increased, NO production was inhibited, which may be anti-inflammatory effect.Applications: These results suggest that orchid leaf ethanol extracts is not cytotoxic, and it is highly to be used as an anti-aging cosmetic ingredient due to its excellent antioxidant and anti-inflammatory effects.